-20x-10=-6-12x

Simple and best practice solution for -20x-10=-6-12x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20x-10=-6-12x equation:



-20x-10=-6-12x
We move all terms to the left:
-20x-10-(-6-12x)=0
We add all the numbers together, and all the variables
-20x-(-12x-6)-10=0
We get rid of parentheses
-20x+12x+6-10=0
We add all the numbers together, and all the variables
-8x-4=0
We move all terms containing x to the left, all other terms to the right
-8x=4
x=4/-8
x=-1/2

See similar equations:

| 1/2(t2+1)(t2-1)=0 | | (8x-8)=(7x-8) | | n+10+(n-6)+10=50 | | □x+2=4x+□ | | 1/2t4-1/2=0 | | -20-10=-6-12x | | 17/16=y/6 | | -2(2y-2)=-12 | | 3+(4c)=11 | | 50x^2-128=0 | | 48+0.99w=1.29w | | x^2+(10-3x)^2=50 | | -x2+6x-9=0 | | 8x+13-3x=8 | | 7x-7=45 | | 3x2-12x+3=0 | | -85=5(4x+3) | | (2x-5)2-9=0 | | 3g/6(g/8)=42 | | 7u/3=49 | | -3/12x=8/12 | | 5/4y=35/8 | | 0.05x+(25-x)*0.25=5.05 | | 3000+200x=6000+125x | | x-17=84 | | -6|3-9x=-18 | | 2(2a-1)=6 | | (x^2+7)x(x-4)=0 | | (30/x^2-25)-(3/x-5)=(8/x-5) | | 10a-8=73 | | (x2+7)x(x-4)=0 | | 2t(15t-60)=0 |

Equations solver categories